Serum and Urine Interleukin-6 and Interleukin-8 Levels Do Not Differentiate Acute Pyelonephritis from Lower Urinary Tract Infections in Children - Al Rushood M; AL-Eisa A; AL-Attiyah R (Dove Medical Press, 2020)
Maysoun Al Rushood,1 Amal AL-Eisa,1 Rajaa’ AL-Attiyah2 1Department of Pediatrics, Faculty of Medicine, Health Sciences Center, Kuwait University, Kuwait City, Kuwait; 2Department of Microbiology, Faculty of Medicine, Health Sciences Center, Kuwait University, Kuwait City, KuwaitCorrespondence: Maysoun Al RushoodDepartment of Pediatrics, Faculty of Medicine, Kuwait University, P.O. Box 24923, Safat 13110, Kuwait City, KuwaitTel +965-25319486Fax +965-25338940Email maysounrushood@hsc.edu.kwBackground: Urinary tract infection (UTI) is common in pediatrics. Infection of the upper urinary tract may cause renal scarring, and subsequently renal failure and hypertension. Permanent renal damage has been suggested to be caused by the host inflammatory response. Therefore, it is crucial to understand the host defense mechanisms against such infection in order to make timely diagnosis. The aim of this study was to evaluate interleukin-6 (IL-6) and IL-8 as potential biomarkers in differentiating acute pyelonephritis (AP) from cystitis (Cys) in children.Methods: Forty-three children (21 with AP and 22 with Cys) were included. Serum and urinary IL-6 and IL-8 were measured during the acute phase (within 12 hours of presentation) and the convalescent phase (8 weeks post-infection). Thirty-eight healthy children were included as controls.Results: During the acute phase, the mean urinary IL-6 level in the Cys group was significantly higher than that in the controls (17.8 pg/mL vs 14.8 pg/mL, P=0.03), while the serum levels were significantly higher in both the Cys and AP groups than in the controls (19.5 pg/mL, 19.4 pg/mL, 15 pg/mL, P=0.005 and 0.02, respectively). During the convalescent phase, serum and urinary IL-6 levels were higher in patients than in controls. Urinary IL-8 levels were significantly higher in both the AP and Cys groups compared to controls (206.5 pg/mL, 291.8 pg/mL, 89.4 pg/mL, P=0.05 and 0.02, respectively) during the acute phase. Serum IL-8 was not significantly different between the 3 groups. Nonetheless, no significant differences were found between the AP and Cys groups, in urinary or serum levels of IL-6 or IL-8, during both phases.Conclusion: IL-6 and IL-8 levels are elevated in patients with UTI. However, the levels did not differentiate between AP and cystitis. Further studies are warranted to evaluate their roles as indicators of the site of UTIs.Keywords: cystitis, IL-6, IL-8, pyelonephritis, UTI